The Prognostic Value of Blood-Based Biomarkers in Patients With Testicular Diffuse Large B-Cell Lymphoma - Yang, Jing; Guo, Xinli; Hao, Jianqi; Dong, Yiting; Zhang, Tao; Ma, Xuelei (Frontiers in Oncology, 2019)
Objectives: Previous studies have reported the prognostic value of neutrophil/lymphocyte ratio (NLR), platelet/lymphocyte ratio (PLR), lymphocyte/monocyte ratio (LMR), and systemic immune-inflammation index (SII). However, the prognostic performance of these indices in patients with testicular lymphoma has not yet been studied. This study was to systematically evaluate the role of NLR, PLR, LMR, and SII in predicting survival for patients with testicular diffuse large B-cell lymphoma. Methods: In this study, 28 patients with testicular diffuse large B-cell lymphoma were enrolled. We performed univariate and multivariate analyses to assess associations of indices incorporating blood cell counts with progression-free survival (PFS) and overall survival (OS). Results: The results of univariate analysis revealed that International Prognostic Index (IPI) score (p = 0.010, p = 0.034, respectively), NLR (p = 0.003, p = 0.025, respectively), and LMR (p = 0.004, p = 0.010, respectively) were significantly associated with PFS and OS. Lactic dehydrogenase (LDH) (p = 0.017), absolute neutrophil counts (p = 0.018), absolute monocyte counts (p = 0.001), and SII (p = 0.005) were significantly associated with the risk of disease progression, while ECOG performance status (p = 0.016) was shown to be related to the risk of death. In the multivariate analysis, NLR (HR 9.069, p = 0.001) and absolute monocyte counts (HR 37.076, p = 0.001) were shown to be independently associated with risk for disease progression, while LMR (HR 0.077, p = 0.028), and ECOG performance status (HR 20.013, p = 0.026) were proved to be independent predictors of OS. Conclusions: In conclusion, high absolute monocyte counts, high NLR and low LMR may indicate unfavorable prognosis in testicular diffuse large B-cell lymphoma patients. Since indices incorporating blood cell counts are low cost parameters, they may provide additional prognostic value beyond standard clinicopathological parameters. However, further studies are needed to confirm our findings.